Infecciones vaginales en gestantes adolescentes en pretérmino como desencadenante del falso trabajo de parto en el Hospital León Becerra Camacho. Noviembre 2023 - abril 2024. - Espín Yépez, Roxana Stefania (2024)
The following document contains the research titled "Prevalence of Vaginal Infections and their Impact on Preterm Pregnant Adolescents: A Study at the León Becerra Camacho Hospital." This study aimed to investigate the prevalence of vaginal infections in preterm pregnant adolescents, identify associated risk factors and analyze their relationship with the incidence of false labor. A retrospective analysis of clinical records and diagnostic tests of pregnant adolescents treated at the León Becerra Camacho Hospital during 2023 was carried out. Structured interviews were carried out to collect data on risk factors. Statistical analysis was used to relate the presence of infections to the incidence of false labor. A high prevalence of vaginal infections was found among pregnant adolescents, with a significant correlation between the presence of these infections and the incidence of false labor. Factors such as gestational age, medical history and sexual behavior were identified as risk factors. The results show the need for sexual education programs, equitable access to prenatal health care, and training of health care providers to address the prevention and management of vaginal infections in pregnant adolescents. The importance of early detection and appropriate treatment of vaginal infections during adolescent pregnancy is highlighted, as well as the need for interventions to improve access to prenatal medical care and sexual education.